Drug design strategies focusing on the CXCR4/CXCR7/CXCL12 pathway in leukemia and lymphoma. (1st November 2016) - Barbieri, Federica; Bajetto, Adriana; Thellung, Stefano; Würth, Roberto; Florio, Tullio
ABSTRACT: Introduction : Chemokines control homing and trafficking of leukocytes in bone marrow and lymphoid organs. In particular, CXCL12 and its receptors CXCR4/CXCR7 control the homeostasis of multiple organs and systems. Their overexpression is linked to tumor development, both through a direct modulation of neoplastic cell proliferation, survival, and migration, and, indirectly, acting on the tumor microenvironment which sustains drug resistant tumor stem-like cells. Leukemia and lymphomas frequently display upregulation of CXCL12/CXCR4 in bone marrow that nurtures tumor cells, and confers resistance to conventional chemotherapy, increasing disease relapse. Areas covered : The authors review the molecular and cellular mechanisms by which the CXCL12/CXCR4-7 system supports leukemic bone marrow and how it contributes to leukemia development, and their potential pharmacological targeting. Besides receptor antagonists that directly inhibit leukemic cell proliferation, preclinical and clinical studies demonstrate that CXCR4 inhibition mobilizes leukemic-lymphoma cells from their niches, improving conventional chemotherapy efficacy. Clinically available and experimental pharmacological tools targeting CXCR4/CXCR7 are also described. Expert opinion : Studies have revealed the therapeutic efficacy of combining CXCR4 inhibitors and cytotoxic agents to sensitize leukemic cells, and overcome natural or acquired resistance. However, several issues are still to be unveiled (for example the role of CXCR7) to maximize therapeutic response and reduce potential toxicities.